Comparison of Bite Force in Patients After Treatment of Mandibular Fractures With 3-Dimensional Locking Miniplate and Standard Miniplates. Issue 1 (April 2019) - Singh, Gaurav; Mishra, Madan; Gaur, Amit; Pathak, Dhritiman
Abstract: Background: Fractures of the mandible can be studied and described in anatomic terms, functional considerations, treatment strategies, and outcome measures. The performance of any fixation system depends on multiple factors including plate adaptation, screw placement, bone quality, drilling conditions, and postoperative patient compliance. Bite force assesses masticatory muscle function under clinical and experimental conditions. Method: 30 patients with isolated, noncomminuted mandibular fractures were randomly divided into two equal groups. Group 1 patients were treated using 3-dimensional locking miniplates and group 2 patients were treated with standard miniplates. The bite forces were recorded at definite time intervals: preoperatively, and second week, sixth week, third month, and sixth month postoperatively. Result: At 6 weeks postoperative, 3 month postoperative, and 6 month postoperative, the mean bite force was found to be significantly higher among group 1 patients as compared to those in group 2 in all the sites. While at 2 week postoperative, the mean bite force was found to be significantly higher in Group 2 as compared to Group 1 at incisor region. Conclusion: The overall results of the present study show better performance in bite force for the 3-dimensional locking miniplate when compared with standard miniplates.